Accuracy of Bioelectric Impedance Analysis Devices to Estimate Body Fat and Fat-Free Mass in College Women Athletes - Ashly Hilfer; Allison Oligchlaeger; Madison Henderson; Molly Whitehead; Jana Arabas; Jerry Mayhew; Jeremy Houser (International Journal of Strength and Conditioning, 2023)
Background: Body composition is frequently measured in women athletes to evaluate training changes, assist in dietary planning, and avoid the female athlete triad. Measurements to monitor %fat and fat-free mass (FFM) can provide valuable information for coaches and athletes throughout the training process. However, questions remain concerning the accuracy of various methods used to measure %fat. The purpose of this study was to assess the accuracy of bioelectric impedance analysis (BIA) devices to estimate %fat and FFM compared to dual-energy X-ray absorptiometry (DXA) in college women athletes.